AUTHORITY DELEGATION IN ORGANIZATION: LESSONS FROM 7TH CENTURY - EARLY ISLAMIC ERA - Mohd Balwi, Mohd Abd Wahab Fatoni; Sarif, Suhaili; Lubis, Asmuliadi (Journal of Al-Tamaddun, 2018)
Authority delegation is an essential element in management. Organizations need to be cautious in the matter, as the decisions may determine its survival. It is not uncommon to see organizations taking a longer time to fill a position of authority; and in some cases the positions can remain unfilled as no one was deemed fit to hold the position. Delegation of authority requires meticulous consideration of all factors taking into account the complexity of circumstances faced by organizations. This article attempts to look at authority delegation as practiced in 7th century – early Islamic era with a special reference during the time Prophet Muhammad (SAW). Based on the sīrah, it was found that even though Prophet Muhammad (SAW) was the spiritual and political leader of the Muslim society, authority delegation was commonly practiced in various circumstances during his era.